Trabeculae In The Egretal (Egretta garzetta) Cervical Vertebrae - Choirudin, Faris; Nyawiji, Kholifah; Priyambodo, Wahyu (Proceeding International Conference on Science and Engineering, 2020)
The egretta bird (Egretta zegretta) has a body size of 55-65 centimeters, it is wings stretches 88-106 centimeters, has a long neck and typical neck like the letter “S”. The purpose of this research is to find out the anatomical structure of trabeculae in the egretta bird. To find out the trebeculae in the egretta bird, meat on the neck cleaned. Then, each bone segment is cut and sanded on the ventral and lateral part until spongiosa tissue (trabeculae) is seen, and transversely cut. The observation result show that on the C6 bone segment has a trabecular structure more dense comepared to the structure of the trabelucae in other bone segments. That is because in the C6 bone segment gets pressure from top and bottom, so C6 bone segment stronger.